Customization of hormone therapy in women with autosomal dominant polycystic kidney disease (ADPKD): actionable strategies and future perspectives - Martina Catania; Micaela Petrone; Liliana Italia De Rosa; Rebecca S. Degliuomini; Kristiana Kola; Chiara Lupi; Matteo Brambilla Pisoni; Stefano Salvatore; Massimo Candiani; Giuseppe Vezzoli; Maria Teresa Sciarrone Alibrandi (AboutScience Srl, 2024)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetically inherited kidney disease and the fourth leading cause of renal replacement therapy worldwide. It is characterized by the development of multiple cysts in the kidneys and in other organs, the increase in renal volume and the progressive loss of renal function. ADPKD outcome seems to be sensitive to hormonal fluctuations, particularly those of sex hormones. Despite the limited literature available, this review presents the first comprehensive overview of contraception and hormonal replacement therapy in women with ADPKD, delving into the risks and benefits associated with different contraceptive methods, including hormonal, intrauterine devices, and non-hormonal approaches. It also explores personalized strategies for contraception based on the severity of renal disease and the presence of comorbidities. Although the protective role of female sex hormones in slowing the progression of renal failure is acknowledged, hormonal therapy in women with ADPKD remains intricate and challenging due to its potential impact on liver disease progression. Women with ADPKD typically experience a slower progression of renal disease compared to men, largely influenced by hormonal dynamics. This literature review underscores the importance of a multidisciplinary assessment and a thorough patient discussion to identify the most suitable contraceptive method for each woman affected by polycystic kidney disease.